A lithium phosphate solid electrolyte for preparing lithium battery and preparation method thereof
By using magnetron sputtering technology to form a sputtering layer in lithium phosphate solid electrolyte, combined with the treatment method of matrix material and intermodulation modification additive, the problem of insufficient performance of lithium phosphate solid electrolyte in the prior art under high magnification and multiple cycle conditions is solved, and higher ionic conductivity and better stability are achieved.
Patent Information
- Application Number
- CN202411401485.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing lithium phosphate solid electrolyte has poor capacity retention performance under high magnification conditions and poor performance stability under multiple cycle conditions, which limits the efficiency of the product.
Li3PO4 with a purity of 99.9% was used as the target to form a sputtering layer through magnetron sputtering technology, and combined with the matrix material and intertuning modification additives were improved by ball milling, pressing, sintering and wetting, and finally a solid electrolyte of lithium phosphate was obtained through thermal improvement treatment.
It significantly improves the ionic conductivity performance of lithium phosphate solid electrolyte and the capacity retention performance under high magnification conditions, and enhances the stability of the product under multiple cycle conditions.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a lithium phosphate solid electrolyte for preparing a lithium battery and a preparation method thereof. Background Art
[0002] The lithium ion conductivity of inorganic solid electrolyte materials is comparable to that of organic electrolytes, which can help solve safety issues. Among inorganic solid electrolytes, lithium phosphate solid electrolytes have the advantages of a wide electrochemical window, high chemical stability, easy processing, and non-flammability. They are a good candidate material for solid electrolytes.
[0003] The existing lithium phosphate solid electrolyte has poor ion conductivity performance and poor capacity retention performance under high rate conditions. It is difficult to coordinate and improve the two. At the same time, the product has poor performance stability under multiple cycle conditions, which further limits the product's efficiency. Based on this, the present invention further improves it. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a lithium phosphate solid electrolyte for preparing a lithium battery and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a lithium phosphate solid electrolyte for preparing a lithium battery, wherein the lithium phosphate solid electrolyte comprises a matrix layer and a sputtering layer;
[0007] The sputtering layer uses Li3PO4 with a purity of 99.9% as a target material and is sputtered onto the substrate layer through magnetron sputtering technology. The magnetron sputtering power is 100-150W, the sputtering time is 10 minutes, and the sputtering is completed to obtain the sputtering layer;
[0008] The base layer is a mixture of base material and intermediary modification additives in a weight ratio of 5:2, which are ball-milled, pressed into shape, and then sintered;
[0009] Finally, the solid electrolyte is subjected to a wetting improvement treatment and then a thermal improvement treatment to obtain a lithium phosphate solid electrolyte.
[0010] Preferably, the matrix material is prepared by mixing LiOH, La2O3 powder, ZrO2 powder and Ta2O5 powder in a weight ratio of (6-7):2:(1-1.5):0.2.
[0011] Preferably, the preparation method of the intermodulation modification additive is:
[0012] S01: irradiating lanthanum oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated lanthanum oxide after the irradiation is completed;
[0013] 3-5 parts of irradiated lanthanum oxide and 2-4 parts of nano calcium carbonate are added to 6-10 parts of sodium dodecylbenzene sulfonate solution and mixed well to obtain a lanthanide agent;
[0014] S02: Preparation of Nano Zinc Oxide Modifier:
[0015] S021: First, the nano zinc oxide is mixed with a sufficient amount of sodium alginate solution with a mass fraction of 2-5% to obtain a nano zinc oxide solution;
[0016] S022: 2-5 parts of nano zinc oxide liquid, 1-2 parts of nano silica sol, 1-3 parts of stearic acid and 3-6 parts of dopamine hydrochloride solution are mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a nano zinc oxide modifier;
[0017] S03: 4-7 parts of nano zinc oxide modifier and 2-5 parts of lanthanide agent are immersed in 8-12 parts of silicic acid solution, and then 2-3 parts of silane coupling agent are added, immersed fully, and then washed with water, filtered and dried to obtain an inter-modulation modification additive.
[0018] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%;
[0019] The mass fraction of the silicic acid solution is 4-7%; the silane coupling agent is silane coupling agent KH560.
[0020] Preferably, the ultrasonic power for full immersion is 350-400W, and the immersion time is 20-30min.
[0021] Preferably, the specific operation method of the infiltration improvement treatment is:
[0022] S01: 4-7 parts of sodium lignin sulfonate solution, 2-5 parts of yttrium nitrate solution and 1-3 parts of silane coupling agent KH550 are mixed evenly to obtain a compounding solution;
[0023] S02: Stir and mix the wetting agent and the re-adjusting liquid in a weight ratio of 3:(5-7) to obtain a wetting improvement liquid;
[0024] S03: The solid electrolyte is soaked in a sufficient amount of the soaking improvement solution until the surface of the solid electrolyte is completely soaked, then taken out and dried.
[0025] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the yttrium nitrate solution is 3-5%.
[0026] Preferably, the preparation method of the wetting agent is:
[0027] 2-5 parts of silicon powder and 3-6 parts of silicon carbide whiskers are blended and added into 6-8 parts of chitosan solution with a mass fraction of 2-5%, and then 1-3 parts of carboxymethyl cellulose and 2-5 parts of sodium dodecyl sulfate are added and blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a wetting agent.
[0028] The present invention also provides a method for preparing a lithium phosphate solid electrolyte for a lithium battery, comprising the following steps:
[0029] Step 1: Mix the base material and the intermediary modification additive in a weight ratio of 5:2 and ball mill at a ball milling speed of 550-750 r / min for 1 hour. After the ball milling is completed, wash, filter, dry, press and form into a sheet with a thickness of 1-2 um, and then sinter to obtain a base layer;
[0030] Step 2: Then, Li3PO4 with a purity of 99.9% is used as a target material and is sputtered onto the substrate layer through magnetron sputtering technology to form a sputtered layer, and finally a wet improvement treatment is performed, and then a thermal improvement treatment is performed to obtain the lithium phosphate solid electrolyte of the present invention.
[0031] Preferably, the sintering temperature is 950-1000° C. and the sintering time is 1 h;
[0032] The pressing pressure of the pressing molding is 10~20MPa, and the pressing time is 20min;
[0033] The specific steps of the thermal improvement treatment are:
[0034] First, heat to 350°C at a rate of 1-3°C / min, keep warm for 30 minutes, and finally heat to 800°C at a rate of 2-5°C / min, keep warm for 20 minutes, and finally air cool to room temperature.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The lithium phosphate solid electrolyte for preparing lithium batteries of the present invention is ball-milled with a base material and an intermediary modification additive, and is pressed and sintered to form a base layer, and is sputtered by using Li3PO4 as a target material to form a sputtering layer, and is finally improved by solid electrolyte infiltration, and then improved by heat to obtain a lithium phosphate solid electrolyte. The prepared electrolyte product is assembled into a battery, and the prepared product has excellent ion conductivity performance and product capacity retention performance under high rate conditions, and the two are improved in a coordinated manner. At the same time, the product has significant performance stability under multiple cycle conditions;
[0037] 2. The intermediary modified additive adopts lanthanum oxide and is treated with proton irradiation to stimulate the active efficiency of lanthanum oxide. The lanthanide agent is fully obtained by mixing nano calcium carbonate and sodium dodecylbenzene sulfonate solution. At the same time, nano zinc oxide is treated with sodium alginate solution to improve the dispersion of nano zinc oxide. Then, nano silica sol, stearic acid and dopamine hydrochloride solution are mixed and ball milled. The lanthanide agent is coordinated by an improved nano zinc oxide modifier, and then coordinated with sodium silicate solution and silane coupling agent. The intermediary modified additive is obtained by co-adjusting and co-assisting the raw materials, coordinating and synergizing, and then being added to the product to enhance the ionic conductivity performance of the system and the capacity retention rate performance of the product under high rate conditions, as well as the cycle stability of the product.
[0038] 3. Wetting improvement treatment uses a wetting agent to adjust the compounding liquid. The silane coupling agent, sodium lignin sulfonate solution and yttrium nitrate solution in the compounding liquid are used as a matrix to enhance the interface between the raw materials, improve the electrolyte wetting, optimize the system interface and activity efficiency, and then through subsequent thermal improvement treatment, the density and comprehensive performance of the system are further improved;
[0039] 4. The silicon carbide whiskers in the wetting agent are matched with silicon powder in a whisker-like structure. After being blended and coordinated with chitosan solution, sodium dodecyl sulfate and carboxymethyl cellulose, the resulting wetting agent can better coordinate the silicon carbide whiskers and silicon powder with the compounding liquid, and the silicon carbide whisker structure is matched with the filling and filling property of silicon powder to give full play to the effect of the compounding liquid, so that the electrolyte of the infiltration improvement liquid is better improved, and the product performance effect is further improved. DETAILED DESCRIPTION
[0040] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] A lithium phosphate solid electrolyte for preparing a lithium battery in this embodiment, the lithium phosphate solid electrolyte comprises a matrix layer and a sputtering layer;
[0042] The sputtering layer uses Li3PO4 with a purity of 99.9% as a target material and is sputtered onto the substrate layer through magnetron sputtering technology. The magnetron sputtering power is 100-150W, the sputtering time is 10 minutes, and the sputtering is completed to obtain the sputtering layer;
[0043] The base layer is a mixture of base material and intermediary modification additives in a weight ratio of 5:2, which are ball-milled, pressed into shape, and then sintered;
[0044] Finally, the solid electrolyte is subjected to a wetting improvement treatment and then a thermal improvement treatment to obtain a lithium phosphate solid electrolyte.
[0045] The matrix material of this embodiment is prepared by mixing LiOH, La2O3 powder, ZrO2 powder and Ta2O5 powder in a weight ratio of (6~7):2:(1~1.5):0.2.
[0046] The preparation method of the intermediary modified additive of this embodiment is:
[0047] S01: irradiating lanthanum oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated lanthanum oxide after the irradiation is completed;
[0048] 3-5 parts of irradiated lanthanum oxide and 2-4 parts of nano calcium carbonate are added to 6-10 parts of sodium dodecylbenzene sulfonate solution and mixed well to obtain a lanthanide agent;
[0049] S02: Preparation of Nano Zinc Oxide Modifier:
[0050] S021: First, the nano zinc oxide is mixed with a sufficient amount of sodium alginate solution with a mass fraction of 2-5% to obtain a nano zinc oxide solution;
[0051] S022: 2-5 parts of nano zinc oxide liquid, 1-2 parts of nano silica sol, 1-3 parts of stearic acid and 3-6 parts of dopamine hydrochloride solution are mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a nano zinc oxide modifier;
[0052] S03: 4-7 parts of nano zinc oxide modifier and 2-5 parts of lanthanide agent are immersed in 8-12 parts of silicic acid solution, and then 2-3 parts of silane coupling agent are added, immersed fully, and then washed with water, filtered and dried to obtain an inter-modulation modification additive.
[0053] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%;
[0054] The mass fraction of the silicic acid solution is 4-7%; the silane coupling agent is silane coupling agent KH560.
[0055] In this embodiment, the ultrasonic power for full immersion is 350-400W, and the immersion time is 20-30min.
[0056] The specific operation method of the infiltration improvement treatment of this embodiment is:
[0057] S01: 4-7 parts of sodium lignin sulfonate solution, 2-5 parts of yttrium nitrate solution and 1-3 parts of silane coupling agent KH550 are mixed evenly to obtain a compounding solution;
[0058] S02: Stir and mix the wetting agent and the re-adjusting liquid in a weight ratio of 3:(5-7) to obtain a wetting improvement liquid;
[0059] S03: The solid electrolyte is soaked in a sufficient amount of the soaking improvement solution until the surface of the solid electrolyte is completely soaked, then taken out and dried.
[0060] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%; the mass fraction of the yttrium nitrate solution is 3-5%.
[0061] The preparation method of the infiltrant of this embodiment is:
[0062] 2-5 parts of silicon powder and 3-6 parts of silicon carbide whiskers are blended and added into 6-8 parts of chitosan solution with a mass fraction of 2-5%, and then 1-3 parts of carboxymethyl cellulose and 2-5 parts of sodium dodecyl sulfate are added and blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a wetting agent.
[0063] A method for preparing a lithium phosphate solid electrolyte for a lithium battery in this embodiment comprises the following steps:
[0064] Step 1: Mix the base material and the intermediary modification additive in a weight ratio of 5:2 and ball mill at a ball milling speed of 550-750 r / min for 1 hour. After the ball milling is completed, wash, filter, dry, press and form into a sheet with a thickness of 1-2 um, and then sinter to obtain a base layer;
[0065] Step 2: Then, Li3PO4 with a purity of 99.9% is used as a target material and is sputtered onto the substrate layer through magnetron sputtering technology to form a sputtered layer, and finally a wet improvement treatment is performed, and then a thermal improvement treatment is performed to obtain the lithium phosphate solid electrolyte of the present invention.
[0066] The sintering temperature of this embodiment is 950-1000°C, and the sintering time is 1h;
[0067] The pressing pressure of the pressing molding is 10~20MPa, and the pressing time is 20min;
[0068] The specific steps of the thermal improvement treatment are:
[0069] First, heat to 350°C at a rate of 1-3°C / min, keep warm for 30 minutes, and finally heat to 800°C at a rate of 2-5°C / min, keep warm for 20 minutes, and finally air cool to room temperature.
[0070] Example 1
[0071] A lithium phosphate solid electrolyte for preparing a lithium battery in this embodiment, the lithium phosphate solid electrolyte comprises a matrix layer and a sputtering layer;
[0072] The sputtering layer uses Li3PO4 with a purity of 99.9% as a target material and is sputtered onto the substrate layer by magnetron sputtering technology. The magnetron sputtering power is 100 W, the sputtering time is 10 minutes, and the sputtering is completed to obtain the sputtering layer;
[0073] The base layer is a mixture of base material and intermediary modification additives in a weight ratio of 5:2, which are ball-milled, pressed into shape, and then sintered;
[0074] Finally, the solid electrolyte is subjected to a wetting improvement treatment and then a thermal improvement treatment to obtain a lithium phosphate solid electrolyte.
[0075] The matrix material of this embodiment is prepared by mixing LiOH, La2O3 powder, ZrO2 powder and Ta2O5 powder in a weight ratio of 6:2:1:0.2.
[0076] The preparation method of the intermediary modified additive of this embodiment is:
[0077] S01: irradiating lanthanum oxide in a proton irradiation box for 5 minutes at an irradiation power of 350 W, and obtaining irradiated lanthanum oxide after the irradiation is completed;
[0078] 3 parts of irradiated lanthanum oxide and 2 parts of nano calcium carbonate are added to 6 parts of sodium dodecylbenzene sulfonate solution and mixed thoroughly to obtain a lanthanide agent;
[0079] S02: Preparation of Nano Zinc Oxide Modifier:
[0080] S021: First, the nano zinc oxide is mixed with a sufficient amount of sodium alginate solution with a mass fraction of 2% to obtain a nano zinc oxide solution;
[0081] S022: 2 parts of nano zinc oxide solution, 1 part of nano silica sol, 1 part of stearic acid and 3 parts of dopamine hydrochloride solution were mixed and ball-milled at a speed of 1000 r / min for 2 h. After the ball milling was completed, the mixture was washed with water, filtered and dried to obtain a nano zinc oxide modifier;
[0082] S03: 4 parts of nano zinc oxide modifier and 2 parts of lanthanide agent are immersed in 8 parts of silicic acid solution, and then 2 parts of silane coupling agent are added, immersed fully, and then washed with water, filtered and dried to obtain an inter-modulation modification additive.
[0083] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 2%; the mass fraction of the dopamine hydrochloride solution is 3%;
[0084] The mass fraction of the silicic acid solution is 4%; the silane coupling agent is silane coupling agent KH560.
[0085] The ultrasonic power for full immersion in this embodiment is 350W, and the immersion time is 20 minutes.
[0086] The specific operation method of the infiltration improvement treatment of this embodiment is:
[0087] S01: 4 parts of sodium lignin sulfonate solution, 2 parts of yttrium nitrate solution and 1 part of silane coupling agent KH550 are mixed evenly to obtain a compounding solution;
[0088] S02: The wetting agent and the re-adjusting liquid are stirred and mixed in a weight ratio of 3:5 to obtain a wetting improvement liquid;
[0089] S03: The solid electrolyte is soaked in a sufficient amount of the soaking improvement solution until the surface of the solid electrolyte is completely soaked, then taken out and dried.
[0090] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%; the mass fraction of the yttrium nitrate solution is 3%.
[0091] The preparation method of the infiltrant of this embodiment is:
[0092] 2 parts of silicon powder and 3 parts of silicon carbide whiskers are blended and added to 6 parts of 2% chitosan solution by mass, and then 1 part of carboxymethyl cellulose and 2 parts of sodium dodecyl sulfate are added and blended and ball-milled at a speed of 1000 r / min for 2 hours. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain a wetting agent.
[0093] A method for preparing a lithium phosphate solid electrolyte for a lithium battery in this embodiment comprises the following steps:
[0094] Step 1: The base material and the intermediary modification additive are mixed and ball-milled in a weight ratio of 5:2, the ball milling speed is 550r / min, the ball milling is performed for 1h, and after the ball milling is completed, the mixture is washed, filtered, dried, pressed into a sheet with a thickness of 1um, and then sintered to obtain a base layer;
[0095] Step 2: Then, Li3PO4 with a purity of 99.9% is used as a target material and is sputtered onto the substrate layer through magnetron sputtering technology to form a sputtered layer, and finally a wet improvement treatment is performed, and then a thermal improvement treatment is performed to obtain the lithium phosphate solid electrolyte of the present invention.
[0096] The sintering temperature of this embodiment is 950°C and the sintering time is 1h;
[0097] The pressing pressure of the pressing molding is 10MPa and the pressing time is 20min;
[0098] The specific steps of the thermal improvement treatment are:
[0099] First, heat to 350°C at a rate of 1°C / min, keep warm for 30 minutes, and finally heat to 800°C at a rate of 2°C / min, keep warm for 20 minutes, and finally air cool to room temperature.
[0100] Example 2
[0101] A lithium phosphate solid electrolyte for preparing a lithium battery in this embodiment, the lithium phosphate solid electrolyte comprises a matrix layer and a sputtering layer;
[0102] The sputtering layer uses Li3PO4 with a purity of 99.9% as a target material and is sputtered onto the substrate layer by magnetron sputtering technology. The magnetron sputtering power is 150W, the sputtering time is 10 minutes, and the sputtering is completed to obtain the sputtering layer;
[0103] The base layer is a mixture of base material and intermediary modification additives in a weight ratio of 5:2, which are ball-milled, pressed into shape, and then sintered;
[0104] Finally, the solid electrolyte is subjected to a wetting improvement treatment and then a thermal improvement treatment to obtain a lithium phosphate solid electrolyte.
[0105] The matrix material of this embodiment is prepared by mixing LiOH, La2O3 powder, ZrO2 powder and Ta2O5 powder in a weight ratio of 7:2:1.5:0.2.
[0106] The preparation method of the intermediary modified additive of this embodiment is:
[0107] S01: irradiating lanthanum oxide in a proton irradiation box for 10 minutes at an irradiation power of 400 W, and obtaining irradiated lanthanum oxide after the irradiation is completed;
[0108] 5 parts of irradiated lanthanum oxide and 4 parts of nano calcium carbonate are added to 10 parts of sodium dodecylbenzene sulfonate solution and mixed thoroughly to obtain a lanthanide agent;
[0109] S02: Preparation of Nano Zinc Oxide Modifier:
[0110] S021: First, the nano zinc oxide is mixed with a sufficient amount of sodium alginate solution with a mass fraction of 5% to obtain a nano zinc oxide solution;
[0111] S022: 5 parts of nano zinc oxide solution, 2 parts of nano silica sol, 3 parts of stearic acid and 6 parts of dopamine hydrochloride solution were mixed and ball-milled at a speed of 1500 r / min for 2 h. After the ball milling was completed, the mixture was washed with water, filtered and dried to obtain a nano zinc oxide modifier;
[0112] S03: 7 parts of nano zinc oxide modifier and 5 parts of lanthanide agent are immersed in 12 parts of silicic acid solution, and then 3 parts of silane coupling agent are added, immersed fully, and then washed with water, filtered and dried to obtain an inter-modulation modification additive.
[0113] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 6%;
[0114] The mass fraction of the silicic acid solution is 7%; the silane coupling agent is silane coupling agent KH560.
[0115] In this embodiment, the ultrasonic power for full immersion is 400 W, and the immersion time is 30 min.
[0116] The specific operation method of the infiltration improvement treatment of this embodiment is:
[0117] S01: 7 parts of sodium lignin sulfonate solution, 5 parts of yttrium nitrate solution and 3 parts of silane coupling agent KH550 are mixed evenly to obtain a compounding solution;
[0118] S02: The wetting agent and the re-adjusting liquid are stirred and mixed in a weight ratio of 3:7 to obtain a wetting improvement liquid;
[0119] S03: The solid electrolyte is soaked in a sufficient amount of the soaking improvement solution until the surface of the solid electrolyte is completely soaked, then taken out and dried.
[0120] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 25%; the mass fraction of the yttrium nitrate solution is 5%.
[0121] The preparation method of the infiltrant of this embodiment is:
[0122] 5 parts of silicon powder and 6 parts of silicon carbide whiskers were blended and added into 8 parts of 5% chitosan solution by mass, and then 3 parts of carboxymethyl cellulose and 5 parts of sodium dodecyl sulfate were added and blended and ball-milled at a speed of 1500 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain the wetting agent.
[0123] A method for preparing a lithium phosphate solid electrolyte for a lithium battery in this embodiment comprises the following steps:
[0124] Step 1: The base material and the intermediary modification additive are mixed and ball-milled in a weight ratio of 5:2, the ball-milling speed is 750r / min, the ball-milling is for 1h, and after the ball-milling is completed, the mixture is washed, filtered, dried, pressed into a sheet with a thickness of 2um, and then sintered to obtain a base layer;
[0125] Step 2: Then, Li3PO4 with a purity of 99.9% is used as a target material and is sputtered onto the substrate layer through magnetron sputtering technology to form a sputtered layer, and finally a wet improvement treatment is performed, and then a thermal improvement treatment is performed to obtain the lithium phosphate solid electrolyte of the present invention.
[0126] The sintering temperature of this embodiment is 1000°C and the sintering time is 1h;
[0127] The pressing pressure of the pressing molding is 20MPa, and the pressing time is 20min;
[0128] The specific steps of the thermal improvement treatment are:
[0129] First, the temperature was raised to 350°C at a rate of 3°C / min, kept at this temperature for 30 min, and finally raised to 800°C at a rate of 5°C / min, kept at this temperature for 20 min, and finally air-cooled to room temperature.
[0130] Example 3
[0131] A lithium phosphate solid electrolyte for preparing a lithium battery in this embodiment, wherein the lithium phosphate solid electrolyte comprises a matrix layer and a sputtering layer;
[0132] The sputtering layer uses Li3PO4 with a purity of 99.9% as a target material and is sputtered onto the substrate layer by magnetron sputtering technology. The magnetron sputtering power is 120W, the sputtering time is 10min, and the sputtering is completed to obtain the sputtering layer;
[0133] The base layer is a mixture of base material and intermediary modification additives in a weight ratio of 5:2, which are ball-milled, pressed into shape, and then sintered;
[0134] Finally, the solid electrolyte is subjected to a wetting improvement treatment and then a thermal improvement treatment to obtain a lithium phosphate solid electrolyte.
[0135] The matrix material of this embodiment is prepared by mixing LiOH, La2O3 powder, ZrO2 powder and Ta2O5 powder in a weight ratio of 6.5:2:1.2:0.2.
[0136] The preparation method of the intermediary modification additive of this embodiment is:
[0137] S01: irradiating lanthanum oxide in a proton irradiation box for 7.5 minutes at an irradiation power of 370 W, and obtaining irradiated lanthanum oxide after the irradiation is completed;
[0138] 4 parts of irradiated lanthanum oxide and 3 parts of nano calcium carbonate are added to 8 parts of sodium dodecylbenzene sulfonate solution and mixed thoroughly to obtain a lanthanide agent;
[0139] S02: Preparation of Nano Zinc Oxide Modifier:
[0140] S021: First, the nano zinc oxide is mixed with a sufficient amount of sodium alginate solution with a mass fraction of 3.5% to obtain a nano zinc oxide solution;
[0141] S022: 3.5 parts of nano zinc oxide solution, 1.5 parts of nano silica sol, 2 parts of stearic acid and 4.5 parts of dopamine hydrochloride solution were mixed and ball-milled at a speed of 1250 r / min for 2 h. After the ball milling was completed, the mixture was washed with water, filtered and dried to obtain a nano zinc oxide modifier;
[0142] S03: 5.5 parts of nano zinc oxide modifier and 3.5 parts of lanthanide agent are immersed in 10 parts of silicic acid solution, and then 2.5 parts of silane coupling agent are added, immersed fully, and then washed with water, filtered and dried to obtain an inter-modulation modification additive.
[0143] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 3.5%; the mass fraction of the dopamine hydrochloride solution is 4.5%;
[0144] The mass fraction of the silicic acid solution is 5.5%; the silane coupling agent is silane coupling agent KH560.
[0145] The ultrasonic power for full immersion in this embodiment is 375W, and the immersion time is 25 minutes.
[0146] The specific operation method of the infiltration improvement treatment of this embodiment is:
[0147] S01: 5.5 parts of sodium lignin sulfonate solution, 3.5 parts of yttrium nitrate solution and 2 parts of silane coupling agent KH550 are mixed evenly to obtain a compounding solution;
[0148] S02: The wetting agent and the re-adjusting liquid are stirred and mixed in a weight ratio of 1:2 to obtain a wetting improvement liquid;
[0149] S03: The solid electrolyte is soaked in a sufficient amount of the soaking improvement solution until the surface of the solid electrolyte is completely soaked, then taken out and dried.
[0150] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%; the mass fraction of the yttrium nitrate solution is 4%.
[0151] The preparation method of the infiltrant of this embodiment is:
[0152] 3.5 parts of silicon powder and 4.5 parts of silicon carbide whiskers were blended and added into 7 parts of chitosan solution with a mass fraction of 3.5%, and then 2 parts of carboxymethyl cellulose and 3.5 parts of sodium dodecyl sulfate were added and blended and ball-milled at a speed of 1250 r / min for 2 hours. After the ball-milling was completed, the mixture was washed with water, filtered and dried to obtain the wetting agent.
[0153] A method for preparing a lithium phosphate solid electrolyte for a lithium battery in this embodiment comprises the following steps:
[0154] Step 1: The base material and the intermediary modification additive are mixed in a weight ratio of 5:2 and ball-milled at a speed of 600 r / min for 1 hour. After the ball milling is completed, the mixture is washed, filtered, dried, pressed into a sheet with a thickness of 1.5 m, and then sintered to obtain a base layer;
[0155] Step 2: Then, Li3PO4 with a purity of 99.9% is used as a target material and is sputtered onto the substrate layer through magnetron sputtering technology to form a sputtered layer, and finally a wet improvement treatment is performed, and then a thermal improvement treatment is performed to obtain the lithium phosphate solid electrolyte of the present invention.
[0156] The sintering temperature of this embodiment is 975°C and the sintering time is 1h;
[0157] The pressing pressure of the pressing molding is 15MPa, and the pressing time is 20min;
[0158] The specific steps of the thermal improvement treatment are:
[0159] First, the temperature was raised to 350°C at a rate of 2°C / min, kept at this temperature for 30 min, and finally raised to 800°C at a rate of 3.5°C / min, kept at this temperature for 20 min, and finally air-cooled to room temperature.
[0160] Comparative Example 1.
[0161] The difference from Example 3 is that no interfacial modification additive is added.
[0162] Comparative Example 2.
[0163] The difference from Example 3 is that no lanthanide agent is added in the preparation of the intermodulation modification additive.
[0164] Comparative Example 3.
[0165] The difference from Example 3 is that no irradiated lanthanum oxide is added in the preparation of the lanthanide agent.
[0166] Comparative Example 4.
[0167] The difference from Example 3 is that no nano calcium carbonate is added in the preparation of the lanthanide agent.
[0168] Comparative Example 5.
[0169] The difference from Example 3 is that no nano zinc oxide modifier is added in the preparation of the intermediary modification additive.
[0170] Comparative Example 6.
[0171] The difference from Example 3 is that no nano zinc oxide liquid is added in the preparation of the nano zinc oxide modifier.
[0172] Comparative Example 7.
[0173] Different from Example 3, in the preparation of the nano zinc oxide modifier, the dopamine hydrochloride solution is replaced by water, and no nano silica sol is added.
[0174] Comparative Example 8.
[0175] The difference from Example 3 is that no silane coupling agent is added in the preparation of the interfacial modification additive, and deionized water is used instead of the sodium silicate solution.
[0176] Comparative Example 9.
[0177] The difference from Example 3 is that no wetting improvement treatment is used.
[0178] Comparative Example 10.
[0179] The difference from Example 3 is that no wetting agent is added in the wetting improvement treatment.
[0180] Comparative Example 11.
[0181] The difference from Example 3 is that silicon carbide whiskers and sodium dodecyl sulfate are not added to the wetting agent.
[0182] Comparative Example 12.
[0183] The difference from Example 3 is that silicon powder is not added to the impregnating agent and deionized water is used instead of the chitosan solution.
[0184] Comparative Example 13.
[0185] The difference from Example 3 is that no yttrium nitrate solution and no silane coupling agent KH550 are added to the reconstitution solution.
[0186] Comparative Example 14.
[0187] The difference from Example 3 is that no thermal improvement treatment is used in the preparation method of the lithium phosphate solid electrolyte.
[0188] The products of Examples 1 to 3 and Comparative Examples 1 to 14 were assembled into battery products, and the product performance was tested. The test results are as follows:
[0189]
[0190] It can be seen from Comparative Examples 1 to 14 and Examples 1 to 3 that;
[0191] The product of Example 3 has excellent ionic conductivity, and the product has significant cycle stability after 100 cycles, and the product has significant performance stability under high rate conditions;
[0192] The present invention does not add intermixing modification additives and does not use infiltration improvement treatment, so the performance of the product deteriorates significantly. The synergistic effect of the two is used to achieve the most significant performance effect of the product.
[0193] The performance of the products tended to deteriorate when no lanthanide agent was added to the preparation of the intermediary modification additive, no irradiated lanthanum oxide was added to the preparation of the lanthanide agent, and no nano-calcium carbonate was added to the preparation of the lanthanide agent;
[0194] In the preparation of the intermediary modification additive, no nano zinc oxide modifier was added, no nano zinc oxide liquid was added, dopamine hydrochloride solution was replaced by water in the preparation of the nano zinc oxide modifier, no nano silica sol was added, no silane coupling agent was added in the preparation of the intermediary modification additive, and deionized water was used instead of sodium silicate solution. The performance of the product also showed a trend of deterioration to varying degrees;
[0195] The nano zinc oxide modifier obtained by the specific method of the present invention is combined with the lanthanide agent obtained by the method of the present invention, and the product performance effect is the most significant. The effect of using other methods instead is not as obvious as that of the present invention.
[0196] At the same time, no nano zinc oxide modifier is added in the preparation of the intermediary modification additive, which has a greater influence on the preparation of the intermediary modification additive, and the nano zinc oxide modifier obtained by the specific method of the present invention has the most significant product performance effect;
[0197] No wetting agent was added in the wetting improvement treatment, no silicon carbide whisker or sodium dodecyl sulfate was added to the wetting agent, no silicon powder was added to the wetting agent, deionized water was used instead of the chitosan solution, no yttrium nitrate solution was added to the re-adjusting solution, and no silane coupling agent KH550 was added. The performance of the product also showed a trend of deterioration to varying degrees. The wetting improvement treatment obtained by combining the wetting agent obtained by the specific method of the present invention with the re-adjusting solution had the most significant product performance effect. In the preparation method of the lithium phosphate solid electrolyte, no thermal improvement treatment was used, and the performance of the product also showed a trend of deterioration.
[0198] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0199] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A lithium phosphate solid electrolyte for preparing a lithium battery, characterized in that: The lithium phosphate solid electrolyte includes a matrix layer and a sputtering layer; The sputtering layer uses Li3PO4 with a purity of 99.9% as a target material and is sputtered onto the substrate layer through magnetron sputtering technology. The magnetron sputtering power is 100-150W, the sputtering time is 10 minutes, and the sputtering is completed to obtain the sputtering layer; The base layer is a mixture of base material and intermediary modification additives in a weight ratio of 5:2, which are ball-milled, pressed into shape, and then sintered; Finally, the solid electrolyte is subjected to a wettability improvement treatment and then a thermal improvement treatment to obtain a lithium phosphate solid electrolyte; The preparation method of the intermodulation modification additive is: S01: irradiating lanthanum oxide in a proton irradiation box for 5-10 minutes at an irradiation power of 350-400W, and obtaining irradiated lanthanum oxide after the irradiation is completed; 3-5 parts of irradiated lanthanum oxide and 2-4 parts of nano calcium carbonate are added to 6-10 parts of sodium dodecylbenzene sulfonate solution and mixed thoroughly to obtain a lanthanide agent; S02: Preparation of Nano Zinc Oxide Modifier: S021: First, the nano zinc oxide is mixed with a sufficient amount of sodium alginate solution with a mass fraction of 2-5% to obtain a nano zinc oxide solution; S022: 2-5 parts of nano zinc oxide liquid, 1-2 parts of nano silica sol, 1-3 parts of stearic acid and 3-6 parts of dopamine hydrochloride solution are mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a nano zinc oxide modifier; S03: 4-7 parts of nano zinc oxide modifier and 2-5 parts of lanthanide agent are immersed in 8-12 parts of silicic acid solution, and then 2-3 parts of silane coupling agent are added, immersed fully, and then washed with water, filtered and dried to obtain an inter-modulation modification additive; The specific operation method of the infiltration improvement treatment is: S01: 4-7 parts of sodium lignin sulfonate solution, 2-5 parts of yttrium nitrate solution and 1-3 parts of silane coupling agent KH550 are mixed evenly to obtain a compounding solution; S02: Stir and mix the wetting agent and the re-adjusting liquid in a weight ratio of 3:(5-7) to obtain a wetting improvement liquid; S03: The solid electrolyte is soaked in a sufficient amount of the soaking improvement solution until the surface of the solid electrolyte is completely soaked, and then taken out and dried; The preparation method of the infiltrant is: 2-5 parts of silicon powder and 3-6 parts of silicon carbide whiskers are blended and added into 6-8 parts of chitosan solution with a mass fraction of 2-5%, and then 1-3 parts of carboxymethyl cellulose and 2-5 parts of sodium dodecyl sulfate are added and blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a wetting agent.
2. A lithium phosphate solid electrolyte for preparing a lithium battery according to claim 1, characterized in that: The matrix material is prepared by mixing LiOH, La2O3 powder, ZrO2 powder and Ta2O5 powder in a weight ratio of (6-7):2:(1-1.5):0.
2.
3. A lithium phosphate solid electrolyte for preparing a lithium battery according to claim 1, characterized in that: The mass fraction of the sodium dodecylbenzenesulfonate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%; The mass fraction of the silicic acid solution is 4-7%; the silane coupling agent is silane coupling agent KH560.
4. A lithium phosphate solid electrolyte for preparing a lithium battery according to claim 1, characterized in that: The ultrasonic power for full immersion is 350-400W, and the immersion time is 20-30min.
5. The lithium phosphate solid electrolyte for preparing a lithium battery according to claim 1, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the yttrium nitrate solution is 3-5%.
6. A method for preparing a lithium phosphate solid electrolyte for preparing a lithium battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Mix the base material and the intermediary modification additive in a weight ratio of 5:2 and ball mill at a ball milling speed of 550-750 r / min for 1 hour. After the ball milling is completed, wash, filter, dry, press and form into a sheet with a thickness of 1-2 um, and then sinter to obtain a base layer; Step 2: Then use Li3PO4 with a purity of 99.9% as the target material and sputter it onto the substrate layer through magnetron sputtering technology to form a sputtered layer. Finally, it is subjected to infiltration improvement treatment and then thermal improvement treatment to obtain a lithium phosphate solid electrolyte.
7. The method for preparing a lithium phosphate solid electrolyte for preparing a lithium battery according to claim 6, characterized in that: The sintering temperature is 950~1000℃, and the sintering time is 1h; The pressing pressure of the pressing molding is 10~20MPa, and the pressing time is 20min; The specific steps of the thermal improvement treatment are: First, heat to 350°C at a rate of 1-3°C / min, keep warm for 30 minutes, and finally heat to 800°C at a rate of 2-5°C / min, keep warm for 20 minutes, and finally air cool to room temperature.
Citation Information
Patent Citations
Coated solid electrolyte for lithium battery, and all-solid secondary battery using the same
JP2010033732A
Separator and preparation method therefor, secondary battery, battery module, battery pack, and electrical apparatus
WO2024065151A1